The Government Legal Warranty for Consumers in The Purchase of Property in Indonesia - Subekti Subekti; Dudik Djaja Sidarta; Siti Marwiyah; Suyanto Suyanto; Nazli bin Ismail (SASI, 2023)
Introduction: The sale and purchase of houses between developers and buyers often result default, which detrimental to consumers. The state has issued various policies regarding buying and selling houses and legal guarantees for buying and selling houses, but violations still occur and there is no legal guarantee from the state but must be resolved through litigation.